A population-specific reference panel for improved genotype imputation in African Americans - Jared O’Connell (Nature Portfolio, 2021)
O’Connell et al. construct a new genome-wide imputation reference panel comprising 2,269 individuals of Sub-Saharan African ancestries. They adapt DeepVariant to create best practices for reference panel development and generate a high quality, publicly available resource that will further empower high resolution genome-wide imputation efforts in individuals of African ancestries.